CD160 receptor in CLL: Current state and future avenues - Oumeslakht, Loubna; Aziz, Abdel-ilah; Bensussan, Armand; Ben Mkaddem, Sanae (Frontiers in Immunology, 2022)
CD160 is a glycosylphosphatidylinositol (GPI)-anchored cell surface glycoprotein expressed on cytotoxic natural killer (NK) cells and T-cell subsets. It plays a crucial role in the activation of NK-cell cytotoxicity and cytokine production. It also modulates the immune system and is involved in some pathologies, such as cancer. CD160 is abnormally expressed in B-cell chronic lymphocytic leukemia (CLL) but not expressed in normal B lymphocytes. Its expression in CLL enhances tumor cell proliferation and resistance to apoptosis. CD160 is also a potential prognostic marker for the detection of minimal residual disease (MRD) in CLL, which is important for the clinical management of CLL, the prevention of disease relapse, and the achievement of complete remission. In this review, we present an overview of CD160 and its involvement in the pathophysiology of CLL. We also discuss its use as a prognostic marker for the assessment of MRD in CLL.